PENGARUH JOB INSECURITY TERHADAP JOB PERFORMANCE: PERAN MEDIASI SUBJECTIVE WELL-BEING PADA KARYAWAN TETAP BANK X DI SURABAYA SELAMA MASA PANDEMI COVID-19 - Dumei Tiara Dewi; Ida Bagus Gede Adi Permana (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
The welfare felt by employees can present good work results in the form of high-performance appraisals. Job performance is part of the work of employees where this have negative impact on job insecurity because it is considered stressor. Through the availability of subjective well-being, job insecurity can affect job performance when the individual can offer coping with stressors from the influence of job insecurity. A quantitative approach has used in this study. The distribution of the questionnaires obtained in this study was carried by distributing questionnaires to employees who work at Bank X in Surabaya. The population in this study amounted to 104 people who are permanent employees. This researcher used purposive sampling technique for the sampling and the data testing technique used SPSS IBM 26. The results of this study have shown that job insecurity is negatively significant related effect on job performance, then job insecurity is negatively significant related effect on subjective well-being, other results show subjective well-being is positively significant related effect on job performance, and the results of the latest research have shown that subjective well-being can mediate and have a significant effect on the influence of subjective well-being and job performance.